Odpowiedzi

2010-01-18T20:22:42+01:00
3u+2v=2/×-2
5u+4v=6
-6u-4v=-4
5u+4v=6
-u=2
u=-2
-6+2v=2
2v=8
v=4
odp u=-2, v =4
2x-3y=10/×5
5x+5y=0/×3
10x-15y=50
15x+15y=0
25x=50
x=2
5y=-10
y=-2 odp x=2, y=-2
2010-01-18T20:25:10+01:00
A)
3u+2v=2/*(-2)
5u+4v=6

-6u-4v=-4
5u+4v=6

-u=-2/:(-1)
u=2

u=2
3*2+2v=2

u=2
6+2v=2

u=2
2v=2-6

u=2
2v=-4/:2

u=2
v=-2

b)
2x-3y=10/*(-5)
5x+5y=0/*2

-10x+15y=-50
10x+10y=0

25y=-50/:25
y=-2

y=-2
2x-3*(-2)=10

y=-2
2x+6=10

y=-2
2x=10-6

y=-2
2x=4/:2

y=-2
x=2

2010-01-18T20:27:47+01:00
A) 3u+2v=2 /(-2)
5u+4v=6

-6u-4v=-4
5u+4v=6

-u=2 /:(-1)
u=-2
5u+4v=6
5*(-2)+4v=6
-10+4v=6
4v=6+10
4v=16 /:4
v=4

b) 2x-3y=10 /*5
5x+5y=0 /*3

10x-15y=50
15x+15y=0

25x=50 /:25
x=2
2x-3y=10
2*2-3y=10
4-3y=10
-3y=10-4
-3y=6 /:(-3)
y=-2